(E)-1-(3-Bromophenyl)-3-(3-fluorophenyl)prop-2-en-1-one - Rajendraprasad, S.; Chidan Kumar, C. S.; Ching, Kheng Quah; Chandraju, S.; Lokanath, N. K.; Naveen, S.; Warad, Ismail (International Union of Crystallography, 2017)
In the title compound, C15H10BrFO, the olefinic double bond adopts an E conformation. The molecule is non-planar as seen by the dihedral angle of 48.92 (11) between the bromophenyl and fluorophenyl rings. The carbonyl group is twisted from the plane of the bromophenyl ring and the olefinic double bond. The trans conformation of the C C double bond in the central enone group is confirmed by the C—C C—C torsion angle of 165.7 (2).